Study on Measuring of Real Estate Speculative Bubble: Evidence from Turkey - Berk, Niyazi; Biçen, Sabriye; Seyidov, Nadire (European Journal of Multidisciplinary Studies, 2022)
The investor’s expectation of future price increases on real estate is causing to further rise of prices. In the 1990s, Turkey’s real estate price / rental income ratio was around 10, now is between 17-20 years. On the other hand, as a result of insufficient innovation and incentive application of industry, some companies have left their core activity and moved to the consruction industry. Studies using time series analysis with Turkey’s data show that GDP growth and interest rates have a great impact on investment decisions of consruction companies. Using Turkstat, Bloomberg and Eurostat data, the empirical part of this study present the relationship between interest rate and GDP growth and consruction investments. The analysis will continue with cross-city-time-series analysis for a sample of 4 well-developed cities of turkey, in terms of construction investments. Finally, measuring the price-to-earnings ratio, the home price-to-rent ratio, the gross rental yield and the house ownership ratio will be compared to those of the metropolitan cities in Europe, whether there is a real estate bubble in Turkey or not.